2012
DOI: 10.1038/npp.2012.151
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-Releasing Factor (CRF)-Induced Disruption of Attention in Rats Is Blocked by the κ-Opioid Receptor Antagonist JDTic

Abstract: Stress often disrupts behavior and can lead to psychiatric illness. Considerable evidence suggests that corticotropin-releasing factor (CRF) plays an important role in regulating the effects of stress. CRF administration produces stress-like effects in humans and laboratory animals, and CRF levels are elevated in individuals with stress-related illness. Recent work indicates that k-opioid receptor (KOR) antagonists can block CRF effects, raising the possibility that at least some of the effects of stress are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 58 publications
3
52
0
Order By: Relevance
“…Recent work further showed that the anxiogenic-like effects of CRF were triggered by CRF1-R activation of the dynorphin/ κ opioid receptor system [59] . These results reveal a connection between CRF and the dynorphin/κ opioid receptor system [70] and support that the CRF-induced dynorphin/κ opioid receptor-dependent pathway is involved in the modulation of anxiety-like behaviors [62] .…”
Section: Rodent Models Of Anxietysupporting
confidence: 72%
“…Recent work further showed that the anxiogenic-like effects of CRF were triggered by CRF1-R activation of the dynorphin/ κ opioid receptor system [59] . These results reveal a connection between CRF and the dynorphin/κ opioid receptor system [70] and support that the CRF-induced dynorphin/κ opioid receptor-dependent pathway is involved in the modulation of anxiety-like behaviors [62] .…”
Section: Rodent Models Of Anxietysupporting
confidence: 72%
“…In this latter instance, these manipulations did not affect choice behavior, suggesting that the mechanisms through which increased CRF transmission alters choice latencies may be dissociable from those involved in biasing the direction of choice. Notably central CRF infusions have been reported to increase choice latencies during tests of attention ( Van't Veer et al, 2012;Beard et al, 2015). These findings suggest that the ability of acute stress to induce 'indecisiveness' and increase processing times for action selection is also mediated in part by increased central CRF transmission.…”
Section: Cognitive/motivational Alterations Induced By Increased Crf mentioning
confidence: 90%
“…An initial study investigated the effects of ICV infusions of three different doses of CRF (rat/human; Tocris Bioscience; 0.25, 1, and 3 μg) on effort discounting. Previous experiments have seen alterations in behavior following ICV infusions ranging from doses as low as 0.1 to 10 μg infused into the ventricular system (Dunn and Berridge, 1990;Cador et al, 1992;Adamec and McKay, 1993;Campbell et al, 2004;Van't Veer et al, 2012). As the maximum solubility of CRF in artificial cerebrospinal fluid is 1 μg/1 μl, the infusion volume for the 3 μg dose was set to 3 μl, whereas for the other two doses, the volume was 1 μl.…”
Section: Drugs and Microinfusion Proceduresmentioning
confidence: 99%
“…It has been suggested that KOR antagonists might have a wide range of indications, including the treatment of depressive-, anxiety-, and addictive disorders (for review, see Carlezon et al, 2009;Wee and Koob, 2010;Tejeda et al, 2012;Carlezon and Carroll, 2013). A general ability to reduce the impact of stress may explain how KOR antagonists can have efficacy in such a wide variety of animal models that would appear to represent different disease states Knoll and Carlezon, 2010;Van't Veer et al, 2012;Carlezon and Carroll, 2013). Partial KOR agonists, which activate KORs with a lower efficacy than DYN and thus may lack the dysphoric effects produced by full agonists, could be useful for the treatment of conditions characterized by elevated motivation (Carlezon et al, 2009).…”
Section: Introductionmentioning
confidence: 99%